The Effectiveness of Stabilization Policy in a Small Open Economy - Martin F.J. Prachowny (Queen's University, Department of Economics, 1972)
A small open economy is forced to operate in a constrained policy environment. Although for some products even a small country may have some monopoly power, in the aggregate these countries approximate more closely the behaviour of price takers than price makers. It is to economies such as these, and not larger or closed economies, that the analysis of this paper is devoted. The extremity of the assumptions is such as to make the analysis totally inapplicable to countries such as the United States. The purpose of the paper, then, is to investigate the characteristics peculiar to a small open economy and to incorporate them in a model which will allow us to discuss the effectiveness of stabilization policy in this constrained environment. In particular, it is proposed to re-examine Mundell's conclusions about monetary and fiscal policy under fixed and flexible exchange rates and to show that, under flexible exchange rates, an optimum policy combination exists that eliminates the trade-off between inflation and unemployment. As is common in these stabilization policy models, growth in factor supplies, and therefore output, is assumed not to exist.
Keywords: 330